Ultrasound Treatment Combined with Rhamnolipids for Eliminating the Biofilm of Bacillus cereus - Ben Niu; Yiming Sun; Yongwu Niu; Shan Qiao (Microorganisms)
Biofilm formation by Bacillus cereus is a major cause of secondary food contamination, leading to significant economic losses. While rhamnolipids (RLs) have shown effectiveness against Bacillus cereus, their ability to remove biofilms is limited when used alone. Ultrasound (US) is a non-thermal sterilization technique that has been found to enhance the delivery of antimicrobial agents, but it is not highly effective on its own. In this study, we explored the synergistic effects of combining RLs with US for biofilm removal. The minimum biofilm inhibitory concentration (MBIC) of RLs was determined to be 32.0 mg/L. Using a concentration of 256.0 mg/L, RLs alone achieved a biofilm removal rate of 63.18%. However, when 32.0 mg/L RLs were combined with 20 min of US treatment, the removal rate increased to 62.54%. The highest biofilm removal rate of 78.67% was observed with 256.0 mg/L RLs and 60 min of US exposure. Scanning electron microscopy analysis showed that this combined treatment significantly disrupted the biofilm structure, causing bacterial deformation and the removal of extracellular polymeric substances. This synergistic approach not only inhibited bacterial metabolic activity, aggregation, and adhesion but also reduced early biofilm formation and decreased levels of extracellular polysaccharides and proteins. Furthermore, US treatment improved biofilm permeability, allowing better penetration of RLs and interaction with bacterial DNA, ultimately inhibiting DNA synthesis and secretion. The combination of RLs and US demonstrated superior biofilm removal efficacy, reduced the necessary concentration of RLs, and offers a promising strategy for controlling biofilm formation in the food industry.